The ELFNET book on failure mechanisms, testing methods, and quality issues of lead-free solder interconnects - Grossmann, Günter; Zardini, Christian (Springer, 2011)
The ELFNET Book on Failure Mechanisms, Testing Methods, and Quality Issues of Lead-Free Solder Interconnects is the work of the European network ELFNET which was founded by the European Commission in the 6th Framework Programme. It brings together contributions from the leading European experts in lead-free soldering. The limited validity of testing methods originating from tin-lead solder was a major point of concern in ELFNET members' discussions. As a result, the network's reliability group decided to bring together the material properties of lead-free solders, as well as the basics of material science, and to discuss their influence on the procedures for accelerated testing. This has led to a matrix of failure mechanisms and their activation and, as a result, to a comprehensive coverage of the scientific background and its applications in reliability testing of lead-free solder joints. The ELFNET Book on Failure Mechanisms, Testing Methods, and Quality Issues of Lead-Free Solder Interconnects is written for scientists, engineers and researchers involved with lead-free electronics